The Effectiveness Of Using The Pinterest Media In Teaching Written Descriptive Text For Seventh Grade Students At SMP N 3 Jepara - Nadya Putri Amalia; Dias Andris S; M. Wahyu Widiyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Students have challenges during the learning process, particularly when it comes to descriptive writing. Most students struggle with coming up with ideas, organizing them, and writing paragraphs. Pinterest media is one of the appropriate media for students to enhance their writing. The aim of this research is to assess the impact of utilizing Pinterest visuals on the writing proficiency of seventh-grade students at SMP N 3 Jepara in composing descriptive text. Additionally, it seeks to identify any notable disparities in students' descriptive writing abilities before and after they are instructed using the Pinterest picture media approach. Data is collected via pre-test, post-test, and questionnaires. This study focused on a single group as the main data and it used a pre-experimental quantitative design. This study's sample size is VII H which has 24 students. Students are required to undergo both a pre-test and a post-test for their writing assessments. These test outcomes are subsequently subjected to analysis employing SPSS statistical software version 22. The findings reveal significant disparities, as evidenced by a hypothesis testing value of 0.000, which is less than the significance level of 0.05. This outcome leads to the acceptance of the alternative hypothesis, which asserts that